Where does the buck stop? Community attitudes to over-lending and over-spending - J. Fear; J. O'Brien (Australasian Accounting, Business and Finance Journal, 2009)
This article explores the results of focus groups and a national survey aimed at discovering how ordinary Australians feel about lending and borrowing practices, in the context of high levels of consumer debt. This research, carried out by The Australia Institute in 2007, found a strong community belief that lenders and regulators, rather than individual consumers, were primarily responsible for excessive debt. Many Australians reported feeling uncomfortable about the way that credit is pushed on vulnerable and ill-informed consumers; advertising and marketing were believed to be partly responsible for poor financial decision-making. The authors propose a number of practical policies to improve the environment in which consumers make financial decisions, including a more helpful disclosure regime.
Keywords: financial decision making; corporate ethics; lending behaviour; advertising; focus groups